Influencia del taller "ENGLISH ADVENTURE" en el desarrollo de la habilidad del speaking del idioma ingles en los estudiantes del 1° grado "A" del nivel secundaria de la I.E. José María Arguedas - distrito de Cacatachi - 2013 - Flores Gonzales, Rosa Isabel (2013)
The present research propose the educational strategy ENGLISH ADVENTURE, that contains a set of interactive oral activities for developing the speaking skill of the English language in the students from 1st grade "A' of the secondary level of the Jose Maria Arguedas School- Cacatachi. In this sense, is presented an applied research with experimental level. In theoretical basis of the research is taken as a starting point the Guided discovery learning theory of Bruner, Jerome (1970), as well as theories about strategies and techniques for developing this skill. The design of the research is preexperimental with two measurements: Pre-and Post-test with just one group. The population is constituted on 66 students from 1st grade "A" and "B" of the secondary level of the Jose Maria Arguedas School- Cacatachi taking as sample the 1st grade "A", which is constituted for 15 male and 18 female making 33 students as a total. With this research work is tried to offer a new way to know, improve and optimize the speaking skill of the English language in students, having a positive effect on their academic performance in the new language.